Green synthesis of silver nanoparticles using Eucommia ulmoides leaf extract for inhibiting stem end bacteria in cut tree peony flowers - Ma, Zhanqiang; Zhang, Kaiyue; Guo, Wei; Yu, Weiwei; Wang, Junzhe; Li, Juan (Frontiers in Plant Science, 2023)
Tree peony (Paeonia suffruticosa Andr.) is a popular cut flower among ornamental plants. However, its short vase life severely hinders the production and application of cut tree peony flowers. To extend the postharvest longevity and improve the horticultural value, silver nanoparticles (Ag-NPs) was applied for reducing bacterial proliferation and xylem blockage in cut tree peony flowers in vitro and in vivo. Ag-NPs was synthesized with the leaf extract of Eucommia ulmoides and characterized. The Ag-NPs aqueous solution showed inhibitory activity against bacterial populations isolated from stem ends of cut tree peony ‘Luoyang Hong’ in vitro. The minimum inhibitory concentration (MIC) was 10 mg L−1. Compared with the control, pretreatments with Ag-NPs aqueous solution at 5 and 10 mg L−1 for 24 h increased flower diameter, relative fresh weight (RFW), and water balance of tree peony ‘Luoyang Hong’ flowers. Additionally, malondialdehyde (MDA) and H2O2 content in pretreated petals were lower than the control during the vase life. The activities of superoxide dismutase (SOD) and catalase (CAT) in pretreated petals were lower than that of the control at the early vase stage and higher at the late vase life. Furthermore, pretreatments with Ag-NPs aqueous solution at 10 mg L−1 for 24 h could reduce bacterial proliferation in the xylem vessels on the stem ends by confocal laser scanning microscope (CLSM) and scanning electron microscope (SEM). Overall, pretreatments with green synthesized Ag-NPs aqueous solution effectively reduced bacteria-induced xylem blockage of cut tree peony, resulting in improved water uptake, extended vase life, and enhanced postharvest quality. Therefore, this technique can be used as a promising postharvest technology in the cut flower industry.